On Noncongruence between the Concept and Determination of Death - Bernat, James L. (The Hastings Center report, 2013)
A combination of emerging life support technologies and entrenched organ donation practices are complicating the physician's task of determining death. On the one hand, technologies that support or replace ventilation and circulation may render the diagnosis of death ambiguous. On the other, transplantation of vital organs requires timely and accurate declaration of death of the donor to keep the organs as healthy as possible. These two factors have led to disagreements among physicians and scholars on the precise moment of death. In this article, I suggest that the debate about exactly when a person dies can benefit from distinguishing the strict biological concept of death from the medical standards for determining human death, and I show how an appreciation of the difference between the permanent and irreversible cessation of circulation is helpful in understanding the reasons for the two approaches to determining when death should be declared.